The Effect of Gadgets On The Development of Interest In Reading - Sari, Intan Permata; Karina, Julia; Angraini, Julia Resti; Badriyah, Lailatul (Yayasan Nurul Yakin Bunga Tanjung, 2023)
The type of research used is quantitative research. This research was conducted at MTsS Nurul Ihsan school. With a total student population of 66 people, with a total sample of 16 people using the Cluster Random Sampling technique. The instrument used was a questionnaire with a total of 15 questions. The research results showed that there were 3 people in the category of low interest in reading, 10 people in the category of moderate reading interest and 3 people in the category of high reading interest. In the low category, the average value is 40 with a percentage of 18.75%; in the medium category the average value is 47.6 with a percentage of 62.5%; and in the high category, the average value is 53.3 with a percentage of 18.75%. So the study results show that the average value of students' reading interest on the influence of gadgets is in the medium category, with an average total score of 47.6.